MODEL KEPEMIMPINAN PENDIDIKAN RASULULLAH SAW - Siregar, Diana Riski Sapitri; Musfah, Jejen (Tarbiyatuna Kajian Pendidikan Islam, 2022)
Rasulullah is a reliable manager and leader of Islamic education. The management of Islamic education applied by the Prophet Muhammad is very thick with management values that are currently needed. Indonesia needs role models and leadership and management who believe that positions are responsibilities in this world and in the hereafter, so that leaders can work with heart. The example of leadership is actually in the Prophet Muhammad SAW because he is a leader who gives birth to leaders who are successful in all fields. In this study, the author uses a qualitative research method with a library research approach. The results of this study indicate that all the attitudes and traits of the Prophet Muhammad are categorized into transformational leadership models. Based on the theory, transformational leadership describes the attitude of a leader who is able to influence and direct subordinates in an effective way to achieve predetermined organizational goals.